Clinical and pathologic features of lung cancer expressing programmed cell death ligand 1 (PD-L1). (August 2016) - Shimoji, Masaki; Shimizu, Shigeki; Sato, Katsuaki; Suda, Kenichi; Kobayashi, Yoshihisa; Tomizawa, Kenji; Takemoto, Toshiki; Mitsudomi, Tetsuya
Highlights: A correlation between PD-L1 mRNA expression and H-score was strong in cell lines. PD-L1 was expressed in 22% of adenocarcinomas and 60% of squamous cell cancers. PD-L1 expression was associated with high proliferation and EMT in adenocarcinoma. PD-L1 expression was a significant poor prognostic factor in lung adenocarcinoma. Abstract: Background: Programmed cell death 1 (PD-1) negatively regulates antigen receptor signaling upon binding by either of its ligands, programmed cell death ligand 1 or 2 (PD-L1/2). Blockade of this interaction with either PD-1 or PD-L1 antibodies has been successful in the treatment of human cancer, especially melanoma and non-small cell lung cancer. PD-L1 expression has been proposed as a predictor of tumor response. However, the relationships between PD-L1 expression and various clinicopathological characteristics remain unclear. Materials and methods: PD-L1 expression was examined in 220 non-small cell lung cancer specimens that were consecutively resected at our hospital after validating the E1L3N antibody immunohistochemical assay by comparing IHC and RT-PCR data for lung cancer cell lines. We evaluated the relationships between PD-L1 positivity, several clinical factors and the immunohistochemical expression of epithelial-mesenchymal transition (EMT), cancer stem cell and proliferative markers. Results: PD-L1 was expressed in 22% of lung adenocarcinomas and 60% of squamous cell lung cancers. There was no significant association between PD-L1 expression and clinicopathological features in squamous cell lung cancer. However, in patients with lung adenocarcinoma, PD-L1 expression was significantly correlated with solid subtype histology, vimentin expression, increased Ki-67 labeling index and poor prognosis by multivariate analysis. Conclusion: PD-L1 expression was associated with high proliferative activity and the EMT phenotype in adenocarcinoma but not in squamous cell carcinoma of the lung. PD-L1 expression was a significant poor prognostic factor in patients with lung adenocarcinoma.